Factors influencing Chinese public attitudes toward farm animal welfare - Jiang, Bing; Tang, Wenjie; Cui, Lihang; Wei, Yanjiao (Frontiers in Psychology, 2023)
A comprehensive understanding of current Chinese public attitudes toward farm animal welfare and the relevant influencing factors is essential for improving farm animal welfare and promoting further development of animal husbandry. The attitudes of 3726 respondents in mainland China were investigated using paper and online questionnaires. Three components of attitudes toward farm animal welfare (affective, cognitive, and behavioral) were assessed using 18 items deigned based on the literature review. Influential factors of attitudes toward farm animal welfare were explored via Tobit regression. The results revealed that the Chinese public not only consider farm animals to be emotional and sentient, but are also sympathetic to farm animals that suffer inhumane treatment. Although they have limited knowledge about farm animal welfare, the public believe improving farm animal welfare is beneficial, especially for food safety and human health. The Chinese public prefer regulation policies to incentive policies for improving farm animal welfare. The main factors influencing attitudes toward farm animal welfare included gender, age, education, monthly household income, area of residence, farm animal raising experience, and attention to farm animal welfare events. The effect of these influencing factors on attitudes varied. These findings provide a basis for improving Chinese public attitudes toward farm animal welfare. The implications of formulating and implementing effective policies to improve the Chinese public attitudes toward farm animal welfare were discussed.